Grain yield of maize varieties of different maturity groups under marginal rainfall conditions - Oluwaranti, A.; Fakorede, M.A.B.; Badu-Apraku, Baffour (National Library of Serbia, 2008)
This study was conducted to evaluate the yield performance of different maturity groups of maize varieties at different planting dates under the marginal rainfall conditions of the rainforest ecology of Nigeria and identify the high yielding ones. The maize varieties were evaluated on five and three different planting dates in 2001 and 2005 late cropping seasons respectively. Seven planting dates were used in 2002 and 2006 early cropping seasons. All plantings were done at a weekly interval. Data were obtained on grain yield and yield components. Grain yield and yield components decreased as planting was delayed in the late seasons while in the early seasons they showed contrasting trend. To obtain optimum yield for the maturity classes evaluated, the varieties must be planted about the end of August or first week of September for the late season and about the middle of April in the early season. At the optimum planting date TZEE- WSRBCs and ACR 90 POOL16-DT with grain yield of 3.8 tons ha-1 and 6.4 tons ha-1 were the highest yielding varieties in 2001 and 2002 respectively. In 2005 late cropping season, TZECOMP3DT (1.7 tonsha) was the highest yielding while in 2006 early cropping seasons, ACR 95 TZECOMP4C3 (4.37 tonsha) was the highest yielding variety.